Determinants to grand multi parity among women of reproductive age (35-45), at Entebbe regional referral hospital, Wakiso district. A cross-sectional study. - Biira, Janet; Mpamize, Habert; Nansereko, Hasifa; Nalubega, Jane Frank; Akankwasa, Edith (Student’s Journal of Health Research Africa, 2025)
Background The study aims to identify the individual and facility-related determinants of grand multiparity among women of reproductive age (35-45 years) attending Entebbe Regional Referral Hospital in Wakiso District. Methodology A descriptive cross-sectional study design employing a quantitative research method was used, targeting women of reproductive age (35-45 years) attending Entebbe Regional Referral Hospital. A total of 59 respondents were considered, and a simple random sampling technique was used. Results 22(37%) were 39-42 years, 22(37%) had 3-4 children. 58(66%) said it was not easy for them to access family planning information in their location. 32(54%) said their spouses decide on the number of children to have in the family. 48(81%) agreed that gender preferences influenced their desire to have more children. 26(44%) were not informed of the health risk of grand multiparity. 39(51%) had ever experienced unintended pregnancies due to stockouts of contraceptives at the health facility. 24(40%) said insufficient or unclear guidance was given to them on family planning by health workers. 28(47%) were living more than 10 km from the nearest health facility. Conclusion Individually, financial status, limited access to family planning information, lack of decision-making autonomy, and inadequate knowledge about the health risks associated with multiple pregnancies were all key contributors to grand multiparity. Health facility-related determinants, stockouts of contraceptives, geographic barriers such as long distances to health facilities, and prolonged waiting times discouraged women from seeking reproductive health services, thereby contributing to continued high parity. Recommendation The Ministry of Health should ensure consistent availability of contraceptives in all health facilities to prevent unintended pregnancies and support family planning efforts. Health facility administrators should reduce waiting times and improve counseling services to enhance accessibility and effectiveness of reproductive health services.